Identification of biomarkers, pathways and potential therapeutic agents for salt-sensitive hypertension using RNA-seq - Chao, Xiaoying; Jiang, Zhiyuan; Zhong, Guoqiang; Huang, Rongjie (Frontiers in Cardiovascular Medicine, 2022)
Background: Salt-sensitive hypertension (SSH) is a common type of essential hypertension in China. In recent years, although an increasing number of researches have focused on SSH, few studies have been researched on patients with SSH. The objective of this study was to explore the genes and pathways linked with SSH using RNA-sequencing (RNA-seq). Methods: We used RNA-seq technology to analyze the transcriptome of peripheral blood mononuclear cells (PBMCs) of 16 SSH patients and 34 SRH patients. Next, we analyzed the differentially expressed genes (DEGs) using Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway, and Gene Set Enrichment (GSEA) enrichment analysis. Then, Cytoscape was used to construct the protein-protein interaction (PPI) network and the hub genes. Finally, CMAP analysis found that several small molecular compounds could reverse the altered DEGs. Results: A total of 431 DEGs were found in the PBMC samples, including 294 up-regulated and 137 down-regulated genes. Functional enrichment analysis found significant enrichment in immune-related associations such as inflammation, chemokine, and cytokine-cytokine receptor interaction. The hub genes of the two modules were IL-6, IL-1A, CCL2, CCL3L3 and BUB1. In addition, we identified two small molecular compounds (iopromide, iloprost) that potentially interacted with DEGs. Conclusion: This study suggests some potential biomarkers for the diagnosis of SSH. It provides new insights into SSH diagnosis and possible future clinical treatment.